Visualization of Current and Mapping of Elements in Quantum Dot Solar Cells. (17th December 2015) - Niezgoda, J. Scott; Ng, Amy; Poplawsky, Jonathan D.; McBride, James R.; Pennycook, Stephen J.; Rosenthal, Sandra J.
Abstract : The delicate influence of properties such as high surface state density and organic–inorganic boundaries on the individual quantum dot electronic structure complicates pursuits toward forming quantitative models of quantum dot thin films ab initio. This report describes the application of electron beam‐induced current (EBIC) microscopy to depleted‐heterojunction colloidal quantum dot photovoltaics (DH‐CQD PVs), a technique which affords one a "map" of current production within the active layer of a PV device. The effects of QD sample size polydispersity as well as layer thickness in CQD active layers as they pertain to current production within these PVs are imaged and explained. The results from these experiments compare well with previous estimations, and confirm the ability of EBIC to function as a valuable empirical tool for the design and betterment of DH‐CQD PVs. Lastly, extensive and unexpected PbS QD penetration into the mesoporous TiO2 layer is observed through imaging of device cross sections by energy‐dispersive X‐ray spectroscopy combined with scanning transmission electron microscopy. The possible effects of this finding are discussed and corroborated with the EBIC studies on similar devices. Abstract : Electron‐beam‐induced current serves Quantum Dot Solar Cells to visualize current collection within the active layer of multiple quantum dot solar cell devices. Furthermore, scanning transmission electron microscopy elemental mapping is used to reveal an unexpected penetration depth of quantum dots within the mesoporous oxide layer used in these solar cells.